Initial Experience in Using Continuous Arterial Spin-Labeled MR Imaging for Early Detection of Alzheimer Disease - Raji, C.A.; Lee, C.; Lopez, O.L.; Tsay, J.; Boardman, J.F.; Schwartz, E.D.; Bartynski, W.S.; Hefzy, H.M.; Gach, H.M.; Dai, W.; Becker, J.T. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: MR imaging of the brain has significant potential in the early detection of neurodegenerative disorders such as AD. The purpose of this work was to determine if perfusion MR imaging can be used to separate AD from normal cognition in individual subjects. We investigated the diagnostic utility of perfusion MR imaging for early detection of AD compared with structural imaging. MATERIALS AND METHODS: Data were analyzed from 32 participants in the institutional review board−approved CHS-CS: 19 cognitively healthy individuals and 13 with clinically adjudicated AD. All subjects underwent structural T1-weighted SGPR and CASL MR imaging. Four readers with varying experience separately rated each CASL and SPGR scan finding as normal or abnormal on the basis of standardized qualitative diagnostic criteria for observed perfusion abnormalities on CASL or volume loss on SPGR and rated the confidence in their evaluation. RESULTS: Inter-rater reliability was superior in CASL (κ = 0.7 in experienced readers) compared with SPGR (κ = 0.17). CASL MR imaging had the highest sensitivity (85%) and accuracy (70%). Frontal lobe CASL findings increased sensitivity to 88% and accuracy to 79%. Fifty-seven percent of false-positive readings with CASL were in controls with cognitive decline or instability within 5 years. Three of the 4 readers revealed a statistically significant relationship between confidence and correct classification when using CASL. CONCLUSIONS: Readers were able to separate individuals with mild AD from those with normal cognition with high sensitivity by using CASL but not volumetric MR imaging. This initial experience suggests that CASL MR imaging may be a useful technique for detecting AD. AAAfrican AmericanADAlzheimer DiseaseCASLcontinuous arterial spin-labeledCHSCardiovascular Health StudyCHS-CSCardiovascular Health Study Cognition StudyFDG-PETfluorodeoxyglucose–positron-emission tomographyLleftMCImild cognitive impairmentMMSEMini-Mental State ExaminationMRIMR imagingPETpositron-emission tomographyRrightrCBFregional cerebral blood flowROCreceiver operating characteristicSPECTsingle-photon emission computed tomographySPGRspoiled gradient-recalled echo